MicroRNA-143 reduces viability and increases sensitivity to 5-fluorouracil in HCT116 human colorectal cancer cells - Borralho, Pedro M. (2015)
MicroRNAs are aberrantly expressed in cancer; microRNA-143 (miR-143) is down-regulated in colon cancer. HCT116 human colorectal cancer cells were used to investigate the biological role of miR-143. Transient miR-143 overexpression resulted in an approximate 60% reduction in cell viability. In addition, stable miR-143 overexpressing cells were selected with G418 and exposed to 5-fluorouracil. Increased stable expression of miR-143 was associated with decreased viability and increased cell death after exposure to 5-fluorouracil. These changes were associated with increased nuclear fragmentation and caspase -3, -8 and -9 activities. In addition, extracellular-regulated protein kinase 5, nuclear factor-kappa B and Bcl-2 protein expression was down-regulated by miR-143, and further reduced by exposure to 5-fluorouracil. In conclusion, miR-143 modulates the expression of key proteins involved in the regulation of cell proliferation, death and chemotherapy response. In addition, miR-143 increases the sensitivity of colon cancer cells to 5-fluorouracil, probably acting through extracellular-regulated protein kinase 5/nuclear factor-kappa B regulated pathways. Collectively, the data obtained in the present study suggest anti-proliferative, chemosensitizer and putative pro-apoptotic roles for miR-143 in colon cancer.. - Fundacao Calouste Gulbenkian [FCG 68796/2004]; Fundacao para a Ciencia e a Tecnologia (FCT), Lisbon, Portugal [PTDC/SAU-GMG/099161/2008]; FCT [SFRH/BD/24165/2005, SFRH/BPD/30257/2006]. - The authors thank Dr Christine Esau, ISIS Pharmaceuticals Inc., for the kind gift of miR-143 overexpression and sensor plasmids. The study was supported by grants FCG 68796/2004 from Fundacao Calouste Gulbenkian and PTDC/SAU-GMG/099161/2008 from Fundacao para a Ciencia e a Tecnologia (FCT), Lisbon, Portugal (to C.M.P.R.); by PhD fellowship SFRH/BD/24165/2005 (to P.M.B.) from FCT; and by postdoctoral fellowship SFRH/BPD/30257/2006 (to R.E.C) from FCT.